PREVALENCE OF PSYCHIATRIC MEDICATIONS USE AMONG MEDICAL STUDENTS IN KSA (CAHIERS MAGELLANES-NS, 2024)
Background: The usage of psychiatric medications has recently increased among medical students as a result of the rising prevalence of psychiatric symptomatology in this population. This comprises analgesics, sedatives, stimulants, opioids, antidepressants, and anxiolytics.Objectives : To assess prevalence level of psychiatric medication, use among medical students in KSA.Methods: A cross-sectional study was conducted in Saudi Arabia; The study’s population are medical student in Saudi Arabia. Validated self-administered questionnaire was randomly distributed among consenting medical student participants. The questionnaire consisted of 26 questions assessing the level of prevalence of psychiatric medications among medical students, the type of medications used, indication, the duration of their use, and the side effect associated with their use. Data was entered and analyzed by using IBM Statistical Package for the Social Sciences (SPSS) version 23.0.Results: The study included 480 participants, 60% were females and 40% were males. One quarter of participants use psychiatric medications now or used it before. The majority of respondents (35.0%) reported using these medications within the past 3 months, with a smaller percentage (9.2%) reporting usage three times in a lifetime. Depression was the most common indication for medication use (68.3%), followed by anxiety (59.2%), while bipolar disorder, ADHD, and other indications were reported less frequently (5.8% or less). More than half of the respondents (50.8%) reported an increase in medication dosage after use, and a slight majority (55.0%) reported changing their treatment plan more than once. 75.0% of respondents began using medication after entering medical college, with varying percentages of respondents beginning medication use in different years, the highest being in the third year (25.8%) and the lowest in the sixth year (3.3%).Conclusion: In conclusion, psychiatric medication use is relatively common among medical students in KSA.  There is a significant correlation between age, marital status, gender, monthly income, and academic year in psychiatric medication usage. Age increases the per-centage of individuals using psychiatric medications, while single individuals have higher us-age rates. Gender also plays a role, with females having higher usage rates. However, no significant relationship exists between location or student GPA with psychiatric medication usage.